2018
DOI: 10.1002/ehf2.12256
|View full text |Cite
|
Sign up to set email alerts
|

Risk of stroke and bleeding in patients with heart failure and chronic kidney disease: a nationwide cohort study

Abstract: AimsThe aim of this study was to assess the prognostic value of chronic kidney disease (CKD) in relation to ischaemic stroke, intracranial haemorrhage, major bleeding, and all‐cause death in heart failure patients without atrial fibrillation.Methods and resultsIn this observational cohort study, heart failure patients without atrial fibrillation were identified using Danish nationwide registries. Risk of stroke, major haemorrhage, and death were calculated after 1 and 5 years to compare patients with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The increased risk of bleeding may be due to platelet dysfunction, prolonged bleeding time, and small vessel disease associated with CKD [ 29 ]. Furthermore, the association of CKD with HF episodes confers an extra risk for BE [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of bleeding may be due to platelet dysfunction, prolonged bleeding time, and small vessel disease associated with CKD [ 29 ]. Furthermore, the association of CKD with HF episodes confers an extra risk for BE [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…85 In the Danish nationwide registry, among patients with HF, those with chronic renal disease had a 30% higher stroke risk compared to patients without. 86 Beside these risk factors, any (systemic) clinical characteristics that may increase the likelihood of thrombus formation may further add to the HF-related risk of stroke, including chronic inflammatory diseases and venous vascular comorbidities.…”
Section: Stratification Of Stroke Risk In Heart Failure Patientsmentioning
confidence: 99%
“…Renal function is related to higher stroke risk in patients with HF 85 . In the Danish nationwide registry, among patients with HF, those with chronic renal disease had a 30% higher stroke risk compared to patients without 86 …”
Section: Stratification Of Stroke Risk In Heart Failure Patientsmentioning
confidence: 99%
“…Several studies investigated the impact of renal function on stroke risk in HF. Melgaard et al showed an increased risk of ischemic stroke and intracranial bleeding in HF patients with stable chronic kidney disease, but this association could only be found in patients without renal replacement therapy [ 70 ]. These findings are in agreement with the results of another study showing an association between estimated glomerular filtration rate and stroke risk in HF patients [ 64 ].…”
Section: Risk Stratification Of Stroke In Hfmentioning
confidence: 99%